UNDERSTANDING THE LIVESTREAMING E-COMMERCE PHENOMENON IN INDONESIA: A LITERATURE REVIEW - Azmen Kahar; Yulia Hendri Yeni; Syafrizal; Sari Lenggogeni (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Livestreaming e-commerce has emerged as one of the fastest-growing digital business phenomena in Indonesia in recent years. This phenomenon integrates real-time streaming technology with electronic commerce activities, creating an interactive and immersive shopping experience. This study employs a qualitative literature review approach to analyze the development, characteristics, and impact of livestreaming e-commerce in Indonesia. Through the analysis of 95 articles from various academic databases, this research identifies factors driving the adoption of livestreaming e-commerce, emerging business models, and challenges and opportunities faced. The results show that livestreaming e-commerce in Indonesia is driven by high internet penetration, changing consumer behavior, and digital ecosystem support. Major platforms such as TikTok Shop, Shopee Live, and Instagram Live have become catalysts for the growth of this sector. This research also identifies gaps in academic literature regarding regulatory aspects and long-term socio-economic impacts of this phenomenon. This research is expected to contribute to future researchers, especially those studying the livestreaming e-commerce phenomenon.